A Misdirected Patient Transfer Raises Emergency Medical Treatment and Labor Act Liability Issues. Issue 8 (August 2016) - McDonnell, William M.; Lawton, Maurice K.; Roback, Mark G.
Abstract : Abstract: Children often require transfer to pediatric hospital emergency departments (EDs) after evaluation in community hospital EDs. Such transfers are regulated by the federal Emergency Medical Treatment and Labor Act. Unusual circumstances, such as logistical errors in the physical transfer of the patient, may increase Emergency Medical Treatment and Labor Act-related liability risks for hospitals and ED physicians.